Prevalence and distribution of hypertension and related risk factors in Jilin Province, China 2015: a cross-sectional study - Bin Liu; Wei Sun; Junduo Wu; Tianyi Li; Xianjing Song; Yangyu Zhang; Yingyu Liu; Longbo Li; Yunpeng Yu; Yihang Liu; Chao Qi (BMJ Open)
Objective This study aimed to investigate the prevalence and distribution of hypertension and its related factors in Jilin province, China.Design A cross-sectional study in four cities and four rural counties in Jilin as part of a national Chinese study.Participants and setting A total of 15 206 participants who were ≥15 years old and were selected using a stratified multistage random sampling method.Main outcome measures The prevalence of hypertension.Results The prevalence of hypertension in Jilin province was 24.7%. Moreover, the prevalence of hypertension increased with age in both sexes, and was higher in men than in women. The modifiable factors that were associated with hypertension were body mass index, smoking and alcohol drinking. The risk factors identified are similar to those in southern China, except smoking, which has no association with hypertension prevalence in the South.Conclusions Age, sex, body mass index, smoking and alcohol drinking were risk factors of hypertension. Control of these related risk factors, especially smoking, may be helpful in the treatment and management of hypertension in Jilin province.